1987
DOI: 10.1111/j.1440-1819.1987.tb00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Autistic Children with Setback Course in Their Infancy

Abstract: This study examines the incidence rate of setback in 80 autistic children, the correlation between the type of onset and clinical features, developmental level and prognosis based on an originally developed questionnaire. Moreover, this study seeks to investigate the possibility that infantile autism might be classified into subgroups by the type of onset. The acquired (including questionably acquired) group consisted of 39 cases (49%), while the natal group was made up of 41 cases (51%). The age when the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 8 publications
2
70
1
Order By: Relevance
“…Our data suggest that, in many cases, ASD has a progressive phase involving developmental arrest, slowing, or even regression in social and/or language systems. This phenomenon has been indicated by retrospective reports of autistic regression [23][24][25][26][27][28] and in one prospective report. 32 In a prospective study of infant AU sibs, Zwaigenbaum and colleagues 32 noted an atypical trajectory of development of attention disengagement.…”
Section: Between-group Comparison Of Developmental Trajectory From 14mentioning
confidence: 91%
See 1 more Smart Citation
“…Our data suggest that, in many cases, ASD has a progressive phase involving developmental arrest, slowing, or even regression in social and/or language systems. This phenomenon has been indicated by retrospective reports of autistic regression [23][24][25][26][27][28] and in one prospective report. 32 In a prospective study of infant AU sibs, Zwaigenbaum and colleagues 32 noted an atypical trajectory of development of attention disengagement.…”
Section: Between-group Comparison Of Developmental Trajectory From 14mentioning
confidence: 91%
“…Up to 50% may display typical development or only mild delays until 15 to 24 months of age, followed by loss of language, communication, and/or social skills. [23][24][25][26][27][28] In a retrospective study of regression in autism, Werner and Dawson 23 compared 12-and 24-month videotapes of children with nonregressive early onset of autism, regressed autism, and typical development. The authors reported that levels of complex babbling, word production, and declarative pointing produced by the early-onset ASD group were lower than those produced by other groups at 14 months of age.…”
mentioning
confidence: 99%
“…Some studies, especially the older reports, demonstrated higher rates of epilepsy in autistic children with a history of regression versus the autistic children without regression (79,80,103,104). These results raised the questions if there is a clinically important relation between epileptiform EEG and/or epilepsy and AR as it is shown in ESES or LKS patients.…”
Section: Controversy About Epilepsy/eeg Abnormalities In Autistic Regmentioning
confidence: 99%
“…Approximetely 1/3 of the parents (%20-56) of autistic children report an early regression in their children (1,3,(77)(78)(79)(80)(81)(82). This regression takes place before 3 years of age, commonly between 18-24 months when the child was in the stage of 3-5 words vocabulary (73,78,83,84).…”
Section: Autistic Regressionmentioning
confidence: 99%
“…When asked about initial concerns regarding their child with ASD, at least 30-50% of parents recall abnormalities dating back to the first year, including poor eye contact [11,12,25], lack of response to the parents' voices or attempts to play and interact [11,12,17,25], and extremes of temperament and behavior ranging from alarming passivity to marked irritability [11,12]. Similarly, several studies of early home videos have revealed behaviors indicative of ASD in children later diagnosed compared to those of typically developing children [2,5,15,18].…”
Section: Motivationmentioning
confidence: 99%